2017
DOI: 10.1186/s12903-017-0337-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the progression of chronic periodontitis using subgingival pathogen levels: a 24-month prospective multicenter cohort study

Abstract: Background: The diagnosis of the progression of periodontitis presently depends on the use of clinical symptoms (such as attachment loss) and radiographic imaging. The aim of the multicenter study described here was to evaluate the diagnostic use of the bacterial content of subgingival plaque recovered from the deepest pockets in assessing disease progression in chronic periodontitis patients. Methods: This study consisted of a 24-month investigation of a total of 163 patients with chronic periodontitis who re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 34 publications
(45 reference statements)
0
25
2
Order By: Relevance
“…Several studies have shown that work tasks and variations in work are associated with job satisfaction and motivating factors among dental hygienists [ 13 , 16 , 18 , 23 ]. The Japanese Dental Hygienist Law restricts the job range of dental hygienists to include the mechanical removal of dental plaque and dental calculi, the topical application of medicament on the tooth surface, dental treatment assistance, and health guidance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that work tasks and variations in work are associated with job satisfaction and motivating factors among dental hygienists [ 13 , 16 , 18 , 23 ]. The Japanese Dental Hygienist Law restricts the job range of dental hygienists to include the mechanical removal of dental plaque and dental calculi, the topical application of medicament on the tooth surface, dental treatment assistance, and health guidance.…”
Section: Discussionmentioning
confidence: 99%
“…The root mean square error of approximation (RMSEA) was used for the fitness index [ 20 ]. To determine the characteristics of the minority subjects who answered strongly disagree for the items regarding willingness to work, a classification and regression tree (CART) analysis was conducted [ 21 23 ]. For the correlation of daily job contents with willingness to work, cross tabulations were constructed and chi-square tests were carried out.…”
Section: Study Population and Methodologymentioning
confidence: 99%
“…In total, 124 subjects successfully completed the study protocol. These 124 patients level analysis are described in our previous report [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial variables were dichotomized based on previous reports [ 22 , 27 29 ]. To differentiate sites based on whether they had more or less than 3 mm of CAL progression, cut-off values were set to minimize the difference between sensitivity and specificity [ 22 24 , 29 ]. The cut-off value of A .…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that some members of this composition, known as “keystone pathogens”, could regulate biofilm virulence and modulate the host immune response 9 , 11 , 13 . Longitudinal studies have shown that periodontal disease progression can be predicted by the levels of Porphyromonas gingivalis ( Pg ) and Treponema denticola ( Td ) in subgingival plaque 3 , 9 , 12 . Moreover, it has been reported that Pg and Prevotella intermedia ( Pi ) are more frequently associated with deeper periodontal pockets 31 .…”
Section: Introductionmentioning
confidence: 99%